Neuropsychological-EEG Activation in Genetic Generalized Epilepsy - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from Lithuanian University of Health Sciences, Kaunas, evaluated the effects of neuropsychological activation (NPA) tasks on epileptiform discharges (ED) in adolescents with idiopathic generalized epilepsy (IGE) and in comparison with hyperventilation and photic stimulation.